Польська Шевченкіана у міжвоєнний період ХХ століття - Яручик, Віктор; Iaruchyk, Viktor (Східноєвропейський національний університет імені Лесі Українки, 2014)
Йдеться про звертання польськими інтелектуалами, перекладачами і науковцями до Тараса Шевченка. Він став найпопулярнішим українським митцем, життя і творчість котрого була найбільш знаною серед поляків. Тут розглядаються публікації про Шевченка у часописах, що зверталися до українського питання. The article describes the treatment of Polish intellectuals, translators and researchers to Taras Shevchenko. Ukrainian genius become the most popular writer, whose life and work were the most famous among the Poles. The author makes an attempt to briefly review the major publications about Shevchenko in the most popular Polish magazine that raised on their pages Ukrainian question. The article also examines some literary translations of short prose and poetry of Taras Shevchenko in Polish. Special emphasis is placed on how Shevchenko was also close to the Polish culture and literature. Polish-Ukrainian literary relations were very strong. Article is one of the samples subsequent researchers pay attention to literary problems interwar period of the twentieth century. Important role in this process took creative legacy of Taras Shevchenko.
Polish Shevchenkiana on the 20−30 years XX century
Keywords: Шевченко; творчість; літературний процес; письменник; перекладацька спадщина; Shevchenko; creativity; literary process; writer; translations